The effects of positive affect on cognitive flexibility and inhibition. - Tan, Clement Ting Yuan. (2012)
The effects of positive affect on cognitive inhibition and flexibility were investigated using two versions of task switching: the positive priming and the total change versions of the Dimensional Change Card Sort Task. Forty-four female undergraduates participated in the study. Positive and neutral affects were elicited by films. A modified version of the Self-assessment Manikin scale was used for the mood manipulation check. The mood manipulation was successful. Participants in the positive mood condition reported significantly higher mood valence than those in the neutral mood condition but no difference in mood intensity. Results showed that although participants performed differently on the two versions of task switching, participants with positive affect did not differ from those with neutral affect on both versions. The findings broadly support Pessoa’s dual competition framework by showing that when a task is relatively simple and the induced positive affect is mild, positive affect has no impact on flexibility and inhibition.